Two new species and one new country record for the Cryptocephalus parvulus group (Coleoptera: Chrysomelidae: Cryptocephalinae) from China - Duan, Wen-Yuan; Wang, Feng-Yan; Zhou, Hong-Zhang (Zootaxa, 2025)
Two new species of the subgenus Cryptocephalus Geoffroy, 1762 are described from China: Cryptocephalus (s. str.) longwangshanus Duan, Wang & Zhou, sp. nov. from Zhejiang, Hunan, and Guangxi; C. (s. str.) yangae Duan, Wang & Zhou, sp. nov. from Sichuan and Yunnan. One species is a new country record from China, Cryptocephalus (s. str.) inhumeralis Pic, 1922. High quality color images and line drawings of adult habitus, aedeagus and other important structures are provided for the new species and the new country record species. All the types of the new species are deposited in the collection of Institute of Zoology, Chinese Academy of Sciences (IZ-CAS).